Factors that influence women’s intention to lead family Businesses in Nairobi, Kenya - Ndolo, A. (Strathmore University, 2024)
In recent years, countries have sought more gender equality and acknowledged the unique contributions that women can make as business leaders and entrepreneurs. Women continue playing an invisible role where they work behind the scenes and take up administrative roles such as moderators and informal advisors. However, studies consistently indicate that family firms that have women leaders show improved performance. Despite family-owned enterprises presenting huge opportunities for female family members to lead, representation of women within these businesses’ leadership is still low. Against this backdrop, this study aimed to investigate the factors that influence women’s intention to lead family businesses in Nairobi, Kenya. The study achieved this aim by meeting three research objectives: to investigate the effect of attitude on women’s intention to lead family businesses in Kenya, investigate the effect of subjective norms on women’s intention to lead family businesses in Kenya, and to investigate the effect of perceived behavioural control on women’s intention to lead family businesses in Kenya. The theory of planned behaviour and the social cognitive theory were used to guide the study and fill the conceptual gap in the literature regarding the behavioural elements that drive women’s fundamental identity shift towards leadership roles in family businesses. Adopting a descriptive research design and a positivism research philosophy, survey questionnaires were used to quantitatively collect data to meet the research objectives. The research used purposive sampling to collect data from 169 2nd and 3rd-generation women kin in family businesses. Data was analysed using both descriptive and inferential analysis. The findings indicate that attitude is a positive but non-significant predictor of women’s intentions to lead family businesses in Kenya. In contrast, the findings have indicated that both subjective norms and perceived behavioural control are strong positive significant predictors of women’s intentions to lead family businesses in Kenya. Keywords: Theory of planned behaviours, attitude, subjective norms, perceived behavioural control, behavioural intentions
Full - text thesis